PENERAPAN METODE PEMBELAJARAN QUANTUM TEACHING BERBANTUAN MYSTERY BOX SEBAGAI UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SD INPRES SANGKARA’NA - Rana Syafiqah, Nabila; Nursalam; Suardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the improvement in student learning motivation through the application of the Quantum Teaching method with the Mystery Box media in Pancasila Education learning for fourth-grade students at SD Inpres Sangkara'na, Gowa Regency. This study used a Classroom Action Research (CAR) approach, implemented in two cycles, each consisting of planning, action, observation, and reflection. The subjects were 16 fourth-grade students at SD Inpres Sangkara'na. Data collection techniques used included observation, questionnaires, interviews, and documentation to determine the improvement in student learning motivation after the implementation of the Quantum Teaching method with the Mystery Box media in the learning process. The results showed that student learning motivation increased in each cycle following the method's implementation. In cycle I, observations showed that the average student learning motivation remained in the sufficient category with a score of 2.0, while questionnaire results showed that the majority of students were in the low category (68.75%). In cycle II, a significant improvement occurred, with the average observation score rising to 3.71, categorized as very good, and questionnaire results showed that student learning motivation was in the high category (81,25%) Interview results also indicated that students became more active, enthusiastic, and courageous in participating in learning. Based on these research findings, it can be concluded that the application of the Quantum Teaching method, supported by the Mystery Box, can increase student learning motivation in fourth-grade Pancasila Education at SD Inpres Sangkara'na, Gowa Regency. The Quantum Teaching method helps create an active, enjoyable, and interactive learning environment, while the Mystery Box media fosters curiosity and direct student involvement in the learning process. Therefore, the Quantum Teaching method, supported by the Mystery Box, can be used as an effective alternative learning method to increase elementary school students' learning motivation.